Evaluation of index of cardio-electrophysiological balance and Tp-e/QT ratio in patients with coronary artery ectasia - Alsancak, Yakup; Gürbüz, Ahmet Seyfettin; Saklı, Beyza; İçli, Abdullah (Journal of Surgery and Medicine, 2019)
Aim: Index of cardiac electrophysiological balance (iCEB), calculated as QT interval divided by QRS duration, has been described as a novel risk marker for predicting malignant ventricular arrhythmia. Increased levels of iCEB predict to torsades de pointes (TdP) and decreased levels of iCEB predict to non-torsades de pointes mediated ventricular tachycardia or ventricular fibrillation. The aim of this study is to evaluate arrhythmogenic risk by using iCEB in patients with coronary ectasia (CAE). Methods: Our study, designed as case-control, included 130 patients who were admitted to our outpatient clinic. 75 patients with isolated CAE (study group) and 55 healthy subjects (control group) were included in the study. Both groups underwent a standard 12-lead surface electrocardiogram and Tp-Te interval, QT interval, QRS interval, Tp-Te/QT ratio and QT/QRS ratio (iCEB) of patients were recorded and compared between groups. Results: Tp-e intervals and Tp-e/QT ratio is significantly higher in study group (p=0.001). And, İCEB was found as tend to be numerically higher in study group, but we could not match a statistically difference between groups (p=0.118). Tp-e and Tpe/QT ratio were higher in patients with two or three vessels CAE than one vessel (p value; for Tp-e p=0.024 and Tpe/QT ratio p=0.028). Although iCEB was found as higher with affected number of coronary artery, there was no statistically difference between groups. Conclusion: Our results demonstrate that CAE patients have significantly higher values of Tp-Te and Tp-Te/QT than controls. We need further studies to show increased arrhythmogenesis risk using iCEB for individuals with CAE.